Reasons to Write in Grade 6 and Their Association With Writing Quality - Rocha, Renata S.; Filipe, Marisa; Magalhães, Sofia; Graham, Steve; Limpo, Teresa (Frontiers in Psychology, 2019)
Writing is a particularly complex and demanding task that needs to be mastered to assure students’ success at school. In the last decades, the scientific community has been unanimous about the involvement of cognitive and motivational processes in the learning of writing. However, little is still known about some motivation-related processes, such as the reasons why students write. Therefore, this study analyzed the role of motivation in writing in developing writers, by examining the motives to write of 321 sixth graders. We used the Writing Motivation Questionnaire, which is a new instrument tapping the following motivations for writing: curiosity, involvement, grades, competition, social recognition, emotional regulation, and relief from boredom. Findings confirmed the multidimensional nature of motivations to write and supported the validity and reliability of the instrument. Also, results revealed that the strongest motives to write were grades and curiosity, and that curiosity and social recognition were significant predictors of writing quality, above and beyond attitudes and self-efficacy. Together these findings confirm the key role of motivation in writing and provide validity evidence of the Writing Motivation Questionnaire. This seems a useful tool to better understand the motivational processes involved in learning to write. However, despite the increasing research investment in this area, it is still important to carry out further studies that may contribute to the enrichment of the field of writing motivation.